2017 IEEE 12th International Conference on Global Software Engineering (ICGSE) 2017
DOI: 10.1109/icgse.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Do We Teach the Right Thing? A Comparison of GSE Education and Practice

Abstract: Global Software Engineering (GSE) is a reality for even the smallest companies, so software engineering students need to learn how to work in a globally distributed development context. Many approaches to teaching GSE have been described in the literature. Since the majority of software development is done by engineers working in small or medium sized enterprises (SMEs) we now ask: Are today's students being trained to work effectively in small distributed companies? We surveyed three GSE SMEs to identify whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…This is, in essence, an application of phronesis, involving as it does, the integration of medium and long-term goal-seeking strategies and evaluative reasoning about priorities. In this context, it is worth reviewing the conclusions of Beecham et al [66] who address the question of whether the learning activities undertaken by software engineering students correlate with actual practice in a global software development team, especially within a small or medium-sized enterprise (SME). They report that global software engineering education, while providing technical content, still falls short of providing students with the skills in project management, interpersonal and leadership skills necessary to manage the collaboration processes which are part of the discipline, and this is accentuated in the context of an SME where there is greater fluidity in employee roles and responsibilities.…”
Section: Example Application Area and Discussionmentioning
confidence: 99%
“…This is, in essence, an application of phronesis, involving as it does, the integration of medium and long-term goal-seeking strategies and evaluative reasoning about priorities. In this context, it is worth reviewing the conclusions of Beecham et al [66] who address the question of whether the learning activities undertaken by software engineering students correlate with actual practice in a global software development team, especially within a small or medium-sized enterprise (SME). They report that global software engineering education, while providing technical content, still falls short of providing students with the skills in project management, interpersonal and leadership skills necessary to manage the collaboration processes which are part of the discipline, and this is accentuated in the context of an SME where there is greater fluidity in employee roles and responsibilities.…”
Section: Example Application Area and Discussionmentioning
confidence: 99%
“…Conforming to the challenges reported in the review [Clear et al 2015], potential gaps in GSE-Ed were noted by Beecham et al [2017b]: One was the lack of attention to non-technical aspects such as project management, and interpersonal and leadership skills, and relatedly to student responsibility of projects and their operations. Another gap was the lack of student work in regulated application domains.…”
Section: Gse-ed and The Present Contextmentioning
confidence: 99%
“…The groups decide on all aspects of their projects, including not only technical questions but also the project topic and means of management. GSE-Ed scholars have recently raised the need to increase student responsibility regarding the implementations of GSE-Ed courses [Beecham et al 2017b]. This call was grounded in observations that much of the educational attention readily goes into technical performance instead of generic aspects concerning self-reliance, project management, and interpersonal skills.…”
Section: Introductionmentioning
confidence: 99%
“…Globalization of SE, involving global software engineering (GSE) or global software development (GSD), is one of the most recent trends encountered in the literature. Beecham et al reported an eminent need to address this teaching strategy in recent publications [43,44]. Others suggested how Agile through Scrum methodology can adopt to GSE/GSD [45].…”
Section: Rq1: How Have Contemporary Industry Trends and In Particularmentioning
confidence: 99%